Integration, Regulation, and Collaboration: Three Steps to Combat Climate Change - Leavitt, Victoria (Maine Policy Review, 2023)
Each year the Margaret Chase Smith Library sponsors an essay contest for high school seniors. The essay prompt for 2023 asked students to consider what the proper role of government should be in responding to the issues surrounding climate change. Essays have been edited for length.